Experimental and modelling study on the effect of maltose as a green additive on methane hydrate. (May 2020) - Xu, Zhen; Sun, Qiang; Wang, Yiwei; Luo, Yang; Yue, Gang; Guo, Xuqiang; Li, Xingxun; Yang, Lanying
Highlights: Methane hydrate thermodynamic equilibrium conditions measured in maltose solution. Dissociation enthalpies of methane hydrate in maltose solution were calculated. Kinetics of methane hydrate in maltose solution was measured. Methane hydrate thermodynamic equilibrium conditions calculated in maltose solution. Abstract: The thermodynamic effect and kinetic process of maltose on methane hydrate formation were studied in this work. The gas-liquid-hydrate equilibrium (GLHE) conditions were measured using the isothermal pressure search method in deionized water and maltose aqueous solutions, respectively. The experimental results show that maltose has obvious thermodynamic inhibition effect on methane hydrate formation. The dissociation enthalpies (Δ H diss ) of methane hydrate in different solutions remain quite uniform, which indicates that maltose has not been involved in the formation of hydrate nucleus. The kinetic process of maltose on methane hydrate is evaluated by methane consumption, gas storage capacity (GSC) at 5.00 MPa and 276.15 K. The gas-hydrate steady-state time is longer due to the lower driving force of high concentration maltose aqueous solution at same temperature and pressure. Compared with deionized water, the GSC is lower in a high concentration of maltose aqueous solution. The Chen-Guo hydrate thermodynamic model and Wilson activity coefficient model are applied to calculate the GLHE conditions of methane hydrate in the presence of maltose. The calculation results are well correlated with the experimental values. Maltose is a renewable and edible biological product. Consequently, it is beneficial for the development of green biologically-based additive of hydrate.